Anti-Cariogenic Activity, Cytotoxicity and Chemical Constituents of Zingiber rubens Roxb - Pukumpuang, Wipawan; Chaliewchalad, Pratya (Journal of Food Health and Bioenvironmental Science, 2023)
The objectives of this study were to evaluate the antibacterial activity, cytotoxicity and chemical constituents of Zingiber rubens Roxb. Four parts of the dried plant materials including rhizomes, stems, leaves and fruits were extracted with distilled water and 95% ethanol to obtain crude extracts. The essential oil was derived from the rhizome using steam distillation. After that, the crude extracts and essential oil were screened for antibacterial activity against Lactobacillus casei TISTR 390 and Streptococcus mutans ATCC 25175 using the agar disc diffusion and broth dilution methods. Moreover, the cytotoxicity of the plant extracts was evaluated using MTT assay on Vero cells. The results show that all ethanolic extracts could inhibit the tested bacteria with an inhibition zone ranging from 7.00–8.67 mm and MIC/MBC ranging from 6.25–50 mg/ml. Additionally, the essential oil also effectively inhibited both the bacterial strains with an inhibition zone ranging from 8.17–8.83 mm and MIC/MBC of 250 mg/ml. For in vitro cytotoxic properties, all plant extracts exhibited no toxicity on Vero cells with CC50 between 30.32 - > 1,000 µg/ml. Notably, the essential oil derived from the plant rhizome also revealed no toxicity in vitro with CC 50 of 2.5 µg/ml. Furthermore, the essential oil from the rhizome identified volatile compounds using Gas Chromatography-Mass Spectrometry (GC-MS). Importantly, 2,6,10-Cycloundecatrien-1-one, 2,6,9,9-tetramethyl-, (E,E,E)- or zerumbone is the main compound in essential oil with a % peak area of 20.47 %. Thus, the crude extract and essential oil of this plant could inhibit cariogenic bacteria and display low toxicity on human cells, which may be useful in the development of an antibacterial agent in the future.